Grandparent's Book: Our Story, Our Life - Published by Flame Tree Publishing (UK Flame Tree Publishing, 2005)
Family histories are an endlessly fascinating subject, so this book allows you to keep a record of your life to hand down to future generations. Broken down into 'chapters' on your childhood years, family history, adult years and the next generation, it provides a framework to fill with your memories, stories and photographs. This is a potential treasure trove of family folklore and history.
Includes Colored Illustrations
Keywords: Grandparenting